Affordability In Amortisation Of Public Urban Workforce Home Ownership In Sokoto, Nigeria - Alhaji, Hayatu (2010)

(untitled)
This research study is based purely on the home ownership of public urban workforce housing in Nigeria, with particular focus on affordability in amortisation. Literature on affordability in housing expressed affordability as a relationship between household and their housing situation, and that home ownership affordability can be measured and interpreted by the cost of housing and household’s monthly income, however, it does not specifically address actual home ownership affordability in amortisation despite the fact that the efficiency of the amortisation process in home ownership is assumed to have influence on affordability.